2013
DOI: 10.1038/jcbfm.2013.78
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction in Cerebral Arteries after Subarachnoid Hemorrhage—A Phosphoproteomic Approach

Abstract: After subarachnoid hemorrhage (SAH), pathologic changes in cerebral arteries contribute to delayed cerebral ischemia and poor outcome. We hypothesize such changes are triggered by early intracellular signals, targeting of which may prevent SAH-induced vasculopathy. We performed an unbiased quantitative analysis of early SAH-induced phosphorylations in cerebral arteries and evaluated identified signaling components as targets for prevention of delayed vasculopathy and ischemia. Labeled phosphopeptides from rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Therefore, the combination of treatment with an inhibitor of RhoA, pitavastatin, and an inhibitor of Rho-kinase, fasudil, could extensively prevent cerebral vasospasm after SAH (Naraoka et al, 2013). Furthermore, phosphorylations trigger SAH-induced vasculopathy in cerebral arteries, as determined by quantitative mass spectrometry, including focal adhesion complexes, ERK1/2, calcium calmodulin-dependent kinase II, STAT3, and c-Jun (Parker et al, 2013). Tenascin-C, a matricellular protein, induces cerebral vasospasm via TLR4 and activation of JNK and p38 (Fujimoto et al, 2013; Suzuki et al, 2013).…”
Section: 3 Neurobiological Response After Sahmentioning
confidence: 99%
“…Therefore, the combination of treatment with an inhibitor of RhoA, pitavastatin, and an inhibitor of Rho-kinase, fasudil, could extensively prevent cerebral vasospasm after SAH (Naraoka et al, 2013). Furthermore, phosphorylations trigger SAH-induced vasculopathy in cerebral arteries, as determined by quantitative mass spectrometry, including focal adhesion complexes, ERK1/2, calcium calmodulin-dependent kinase II, STAT3, and c-Jun (Parker et al, 2013). Tenascin-C, a matricellular protein, induces cerebral vasospasm via TLR4 and activation of JNK and p38 (Fujimoto et al, 2013; Suzuki et al, 2013).…”
Section: 3 Neurobiological Response After Sahmentioning
confidence: 99%
“…The reaction was diluted 5-fold with 100 mM TEAB and digested with trypsin (1:50 trypsin/protein) overnight at 37°C. Peptide preparation, stable isotope labeling with isobaric tags for relative and absolute quantitation (iTRAQ; AB Sciex, Framingham, MA), peptide fractionation, and nano-reverse phase liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-MS/MS) was performed as described previously (30). Briefly, 100 g of peptide was labeled with iTRAQ according to the manufacturer's instructions and desalted with hydrophilic-lipophilic balance solid phase extraction (Waters; Milford, MA).…”
Section: Methodsmentioning
confidence: 99%
“…, Parker et al . ). In addition, it has been demonstrated that U0126 treatment in the acute phase following experimental stroke blocks the phosphorylation of ERK1/2 48 h post‐stroke (Maddahi & Edvinsson ).…”
mentioning
confidence: 97%
“…It is demonstrated that U0126 specifically inhibits mitogen-activated protein kinase kinase (MEK) 1/2 and thus inhibits activation of ERK1/2 both in vitro and in vivo , Ahnstedt et al 2015. We have shown that treatment with the MEK1/2 inhibitor U0126 reduces infarct size after experimental focal ischaemic stroke (Henriksson et al 2007) and alleviates neurological deficits 2 days after experimental subarachnoid haemorrhage (Larsen et al 2011, Parker et al 2013). In addition, it has been demonstrated that U0126 treatment in the acute phase following experimental stroke blocks the phosphorylation of ERK1/2 48 h post-stroke (Maddahi & Edvinsson 2008).…”
mentioning
confidence: 98%